STRATEGI PENGUATAN BUDAYA INKLUSI DALAM RANAH PENDIDIKAN DI INDONESIA: KAJIAN LITERATUR - Khoirin Nisa', Syasya; Muntamah, Bening Siti; Nurdibyanandaru, Duta (Jurusan Pendidikan Luar Biasa, 2023)
Inclusive education is education that includes curriculum and management for all children, including those with special needs. It is important to understand the basic concepts of organizing inclusive education, one of which is using the index for inclusion. The purpose of this study is to comprehensively examine the appropriate strategies for strengthening the culture of inclusion in Indonesian inclusive schools. The method used in this research is a literature review, relying on five databases: Google Scholar, ResearchGate, Web of Science, Ebsco, and Scopus. The keywords used in the review were